Histoire des idées politiques et sources littéraires : L'Éducation sentimentale dans le contexte des jugements historiques sur Juin 1848 - Fausto Proietti (Flaubert: Revue Critique et Génétique)
In this paper, Flaubert's novel L'Éducation sentimentale is analyzed as a political text, and placed in its ideological context. The author, who works in the field of the History of Political Ideas, focuses on the way Flaubert depicts the June 1848 Parisian insurrection, which he considers to be the main reason why the novel was perceived as a “subversive” one by his contemporaries. In fact, in order to support his description, Flaubert uses mainly four historical accounts, those written by the “leftist” historians Hippolyte Castille, Daniel Stern, Marc Caussidière and Louis Blanc. Some excerpts from these books are compared to some excerpts from L'Éducation sentimentale, in order to find the similarities between these texts. Finally, it seems that Flaubert's novel has given an important contribution to the circulation of an “anti-bourgeoise” interpretation of the political events which led to the end of the Second Republic, and gave birth to the Second Empire.